(untitled) (Al-Academy, 2024)
The current research, titled “Cultural Landmarks in the Designs of Fabrics and Fashions for Virtual Fashion Shows, and their Network Communication Dimensions,” highlights the importance of the current research in identifying the possibilities of network communication and reflecting cultural landmarks in virtual fashion shows. The research, with its theoretical material, may contribute to the cognitive and scientific aspect of researchers and students in colleges and institutes specialized in design and In particular, designing fabrics, the researcher defined the research problem with the following two questions: 1- How can 3D programs be adapted to design a fashion show that reflects civilization? 2- What is the possibility of benefiting from virtual presentations in reflecting civilization through online communication? It includes a theoretical framework of two sections: The first section: Cultural landmarks in fabric and fashion designs, which dealt with cultural landmarks and their origins, fashion and their relationship to civilization. The second section: Network communication dimensions of virtual displays in fabric and fashion designs, which dealt with the historical development of virtual display and the concept of virtual display and network communication. The most prominent conclusions of the research :The diverse use of cultural monuments and symbols led to the emergence of functional and aesthetic expressive implications